Social Mobilization in the Wake of Coronavirus Disease-19: A Brief Report of a Planned Approach to Community Health in Iran - Javad Mirza-Aghazadeh; Ali Sadaghianifar; Zareipour, Morad Ali; Mohammad Mirza-Aghazadeh-Attari; Kalejahi, Jila Nagavi (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Several plans have been taken by health system to deal with COVID-19. The rapid spread of the virus and the special care that critical patients need put a major pressure on the healthcare system, which may not be able to compensate for its dimensions in various aspects. Therefore, the participation and cooperation of the society in the form of mobilizing the society with the health system will be effective in controlling and preventing this disease. AIM: The overall purpose of this study is to design a community mobilization framework based on the PATCH Model to prevent the spread and control of coronavirus disease. METHODS: This community-based research is a type of health system research (HSR) which designs the community mobilization framework based on the PATCH Model RESULTS: In this project, the community mobilization framework is in the form of the PATCH Model. In this study, interventions and activities will be performed based on the PATCH Model in the neighborhood. Health volunteers consist of popular volunteers, Basij, clerics, neighborhood trustees, donors. After training and issuing the identification card, Corona Anti-Corruption Assistant will start operating. Activities will be purposeful in three areas: education and information, neighborhood surveillance, and disinfection. CONCLUSION: Community mobilization for disease prevention and control in the neighborhood using the PATCH model as presented will be effective.